2020
DOI: 10.12659/msm.920684
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor (FGF) Signaling Protects Against Acute Pancreatitis-Induced Damage by Modulating Inflammatory Responses

Abstract: Science and Technology Plan Projects of Putian City (2018s3001) Background:Acute pancreatitis (AP) is a symptom of sudden pancreas inflammation, which causes patients severe suffering.In general, fibroblast growth factor (FGF) levels are increased and amylase and lipase activities are elevated during AP pathogenesis, but protein concentration are low. However, the mechanism through which FGF signaling regulates AP pathogenesis remains elusive. Material/Methods:The concentrations of PGE2, TNF-a, sCRP, FGF1, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Injection of recombinant FGF1 or FGF2 in rats with AP was shown to inhibit inflammation and the production of inflammatory cytokines and normalize amylase and lipase activities. In contrast, the injection of FGF1 and FGF2 inhibitory antibodies worsened the AP phenotype (Tu et al, 2020).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…Injection of recombinant FGF1 or FGF2 in rats with AP was shown to inhibit inflammation and the production of inflammatory cytokines and normalize amylase and lipase activities. In contrast, the injection of FGF1 and FGF2 inhibitory antibodies worsened the AP phenotype (Tu et al, 2020).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…For example, the herpes virus-mediated overexpression of FGF2 in rat hippocampus attenuated the increase of IL1β expression associated with artificially induced epileptogenesis [ 135 ]. FGF1 or FGF2 administration decreased the inflammatory responses associated with acute pancreatitis in mice [ 136 ]. Furthermore, FGF1 administration decreased the secretion of TNFα and IL6 in a mouse model of diet-induced obesity [ 137 ], and this effect stemmed from the suppression of pro-inflammatory JNK signaling.…”
Section: Cell Processes Underlying the Stimulation Of Tissue Repair By Fgfmentioning
confidence: 99%
“…Fibroblast recruitment into the necrotic area is orchestrated by the coordinated effect of numerous cytokines and growth factors. Among others, fibroblast growth factor and platelet-derived growth factor (PDGF) are the major cytokines that initiate and afterward support fibroblast proliferation and chemotactic activity resulting in the necrotic area encapsulation[ 26 - 28 ]. Clinical observations of Stojek et al [ 29 ] indirectly confirmed this assumption.…”
Section: Discussionmentioning
confidence: 99%